Esg, Eco-Efficiency, And Green Innovation Positively Impact Corporate Financial Performance Through Sustainability Strategies - Kamaluddin, Nurhadi; Maulidya, Nurliana; Saputro, Ilham (Accounting Department,, 2025)
Purpose — This paper aims to investigate the effects of ESG implementation, eco-efficiency practices, and green innovation on the financial performance of mining companies in Indonesia, addressing the increasing demand for corporate sustainability and responsible governance in environmentally impactful industries. Design/methodology/approach — Adopting a quantitative research design, the study employs multiple linear regression analyses on panel data collected from 27 mining firms listed on the IDX for the period 2021–2023, all of which met the criteria for sustainability reporting. Key variables include ESG practices, measurable eco-efficiency, and innovation indices, with data sources triangulated from annual and sustainability reports. Findings — The results reveal that ESG implementation, enhanced eco-efficiency, and green innovation each have a positive and significant effect on company profitability and firm value. ESG contributes to financial outcomes by strengthening social and governance commitments, eco-efficiency supports cost reduction, and green innovation elevates competitive positioning. The findings validate stakeholder theory and resource-based view in the mining sector context. Practical implications — This study highlights actionable strategies for industry leaders and policymakers to integrate sustainability and innovation into corporate governance and operational frameworks, supporting long-term business resilience and risk mitigation in resource-intensive sectors. Originality/value — The paper provides robust empirical evidence from the Indonesian mining sector, an emerging market with high environmental impact. Thus, it contributes to the global discourse on ESG, eco-efficiency, and green innovation as drivers of financial and competitive advantage.